Peringkat kompetensi membaca siswa SMP di antara negara-negara ASEAN berdasarkan pisa - Syafi'i, Imam; Samudro, Rahmad Darmajat Joko (2020)
Indonesia still has a lot of homework, including unequal infrastructure, access to and quality of education, reading resistance, and learning orientation. All of this has an impact on the reading ability of Indonesian students. This article aims to conceptually describe the PISA report related to reading ability compared to ASEAN countries. According to PISA, the reading ability of Indonesian students is functioning 71 out of 79 countries with a score of 371. It is behind Malaysia (56), Brunei (59), and Thailand (66). Only 30% of Indonesian students show good performance at reading level 2, compared to Malaysia (59%), Thailand (40%), Brunei (38%), and the Filipina (19%). In the other hand, the trend of reading ability of Indonesian students is not progressing. Indonesia has a reading trend that is like a hump, while Malaysia and Thailand tend to be flat. This problem of reading skills can be improved by involving many groups: teachers, librarians, parents and government.